Soggettività dissonanti Di rivoluzione, femminismi e violenza politica nella memoria di un gruppo di ex militanti di Lotta continua - Voli, Stefania (Premio Ricerca «Città di Firenze», 2015)
Through the tales of a group of former activists of "Lotta continua", an extra-parliamentary left-wing group, this work traces the cycle of mobilization which Italy went through during the Seventies, in search of the intersections between collective events and subjective experiences. The text focuses on two themes which are considered the tips of a controversial shared memory: political violence on one hand, and neo-feminism on the other. These two steps result fundamental in the process of subjectivation of individual men and women, and their effects can also be traced by observing the individual and collective outcomes of "demobilization".